Vocational education’s growing focus on employability skills: A bibliometrics evaluation of current research - Mochamad Bruri Triyono; Arif Ainur Rafiq; Istanto Wahyu Djatmiko; Govindarajan Kulanthaivel (International Journal of Evaluation and Research in Education (IJERE), 2023)
The study aimed to investigate one of the search’s core issues, ‘employability skills’, and their relationship. It also attempted to recognize the valuable contributions of writers, journals, governments, and institutions worldwide in pursuing employability skills. The quantitative study of bibliographic content is known as bibliometric analysis. Furthermore, it provides a broad view of a study subject that may be subdivided into publications, authors, and journals. This study offers a bibliometric summary of recent research on employability skills. Data was taken from the Scopus database between 2003 and 2022 and examined using VOSviewer software, open refine, tableau public, and Microsoft Excel. The data from the Scopus database are 1,070 documents. Researchers observed that researchers mainly focus on employability skills, higher education, engineering education, curricula, employment, and vocational education. Education and Training journal is the most appropriate journal for contributions, followed by Higher Education, Skills, and Work-based Learning journal, and then the Higher Education Research and Development journal. This study informs researchers by providing insights into basic background knowledge about employability skills for visual and quantitative research. Therefore, this method can observe the research gap in employability skills and more in-depth academic discussions. The study demonstrates how employability skills research has arisen and progressed, as well as prospective future research agendas.